How to image patients with spine pain. Issue 5 (May 2015) - Siemund, R.; Thurnher, M.; Sundgren, P.C.
Highlights: Imaging plays and important role for the evaluation of patients with spine pain. MRI is the best method to evaluateintraspinal lesions, soft tissue and ligaments. CT of the spine is useful to evaluate bony structures. Abstract: Different radiological methods play an important role in the work-up of patients complaining of spine pain. Depending on the symptoms and the suspected underlying etiology different methods are selected. In the following presentation we briefly present the different radiological and magnetic resonance tomography methods that are at hand, give some guidance in which method to use, and present the typical imaging findings in some of the most common conditions that presents with spine pain.